Impact of Human Resource Planning on Organization Financial Performance : A Study of Malaysia Listed Companies - Sopian, Bujang; Rizal, Abu Bakar (2007)
This study investigates the impact of human resource planning on organization financial performance of public listed companies in the main board of Malaysia Stock Exchange. The human resource planning practices were operationalised using five independent variables; 1) environmental scanning, 2) analysis of human resource demand, 3) analysis of human resource supply, 4) integration of human resource panning with organization strategic planning, and 5) integration of human resource planning with human resource management functions. In this study organization financial performance was measure d by perception of management on their financial performance. The data were tested using t-test and multivariate analyses. The result of t-test suggested that there are differences of organization financial performance between companies who implemented human resource planning and companies which did not implement human resource planning. Multiple regression analyses revealed that there are significant impacts of human resource planning on organization financial performance. There are two variables of human resource planning practices namely analysis of human resource supply and integration of human resource planning with human resource management functions indicating positive relationship with organization financial performance. This study offers further understanding on the relationship and association between human resource planning practices and organization performance.